Knowledge and practices on alert signs in pregnant women attended at Hospital Nacional Docente Madre-Niño San Bartolome, Lima, Peru - Ticona Rebagliati, Daniel (2014)
Introduction: According to the millennium development goals, our country must reduce maternal mortality rate in 75%, and the Strategic National Action Plan for Reduction of Maternal and Perinatal Mortality considers reducing the possibilities of complications during pregnancy, labor and puerperium by recognizing the danger signs during pregnancy. Objectives: To determine the level of knowledge and practices on danger signs in pregnant women. Design: Descriptive study. Setting: Hospital Nacional Docente Madre-Niño San Bartolome, Lima, Peru. Patients: Pregnant women in hospitalization and outpatient consultation during June 2013. Interventions: A survey was administered to evaluate knowledge and practices on danger signs during pregnancy. Chi-square test bivariate analysis was used; odds ratio assessed association strength. Main outcome measures: With/without knowledge and practices. Results: Knowledge: 93% of patients considered danger signs as an indicator of risk for both mother and fetus; 100% knew that they should immediately go to a health care center if they showed any of the danger signs. Practices: Patients attended the health care center when they presented seizures (100%), small abdominal growth according to gestational age (100%), dysuria(86.1%), vaginal bleeding (84.4%) and fever (84.2%). Conclusions: The majority of patients considered danger signs as a risk and in case of presenting any of these, they knew they should attend a health care center immediately and they would do it. Further studies are recommended to determine why even when knowing danger signs some women do not goto a health center in time.